Boundedness of the l-Index of Laguerre–Pólya Entire Functions - Bordulyak, M. T.; Sheremeta, M. M. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We investigate conditions on zeros of an entire function f of the Laguerre–Pólya class under which f is a function of bounded l-index.